(untitled) (Revista Lusófona de Educação, 2024)
During the revolutionary period after April 25, 1974, actions took place in several Portuguese schools with a view to replacing school directors, appointed by the authoritarian regime, with elected collegiate bodies. This began in the first days following the coup d’état, which was soon transformed into a revolution, through different processes, initially without authorisation from the first provisional government. Just a month after the beginning of those practices, they were legally recognised and their generalisation to other schools in the country was authorised. Until the end of 1976, there were dynamics of school self-government led by deliberative assemblies, composed of teachers, deciding on multiple issues, well beyond what was permitted by current legislation, to such an extent that these assemblies were legally removed by a decree in December 1974. In practice, however, plenary meetings continued to take place and decide on a wide range of issues, configuring what the author called far-reaching normative infidelities and which, in turn, revealed the capacity to engender subsequent and multiple normative infidelities, with expression in almost all areas of school decision-making and management. Keywords: democratic management; self-government; normative infidelities